Evaluating Research Trends and Gaps in Disaster Literacy within Science Education: A Bibliometric Perspective - Prasetyaningsih Prasetyaningsih; Ida Kaniawati; Lala Septem Riza; Judhistira Aria Utama (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to evaluate research trends, gaps, and global patterns in disaster literacy within science education to identify areas for improvement and provide actionable recommendations for enhancing education strategies in disaster-prone regions. Methodology: A bibliometric analysis was conducted using data from the Scopus database (2000-2024). Tools used include R Studio with the Bibliometrix package for generating visualizations such as co-occurrence networks, word clouds, and trend analyses. The dataset comprises 315 articles selected using “disaster literacy” and "science education". Main Findings: Findings indicate an increasing focus on disaster literacy research, with eminent themes such as technology integration and project-based learning. However, significant gaps remain in contributions from developing nations and the long-term evaluation of disaster literacy programs. Collaborative international research has been identified as a growing trend. Novelty/Originality of this study: This study uniquely combines bibliometric analysis with an evaluative approach to highlight disparities in disaster literacy research and propose strategies for improving curriculum integration and global collaboration. It advances understanding by identifying underexplored areas and providing a foundation for targeted educational interventions.